Nexus Evaluation of Combined Cycle Power Plants based on Water, Energy, and Carbon - Sorour Ghodrati; Nargess Kargari; Forough Farsad; Amir Hossein Javid; Alireza H. Kani (Environmental Energy and Economic Research)
Power generation, water consumption, and carbon emissions from power plants are intertwined. Most power generation technologies require water to cool steam turbines. The amount of water required for different types of power generation technologies varies in different power plants. The electricity sector is also one of the most important sources of greenhouse gas emissions worldwide and the main source of carbon emissions from fuel consumption in gas turbines and boilers. This study aimed to investigate the water, energy, and carbon nexus in the combined cycle power plants of Iran to identify the relationship between power generation, water consumption for electricity generation, and greenhouse gas emissions and ultimately improve the conditions, leading to the protection of the environment. In this study, first, the carbon and water footprints were assessed by LCA, and then, the water-energy nexus was modeled using the REWSS model (Regional Energy and Water Supply Scenarios). The Sankey diagram was then used to show the relationships and the current values for the power generation in the combined cycle power plants. Calculations of water, energy and carbon nexus have been done for 9 power plants and National scale. According to the results Damavand Power Plant had the highest power generation and the lowest WFL (0.068×10-9). The opposite was observed in Khoy Power Plant with the lowest power generation and the highest WFL (0.43×10-9).